2014
DOI: 10.4037/ccn2014412
|View full text |Cite
|
Sign up to set email alerts
|

Designing a Critical Care Nurse–Led Rapid Response Team Using Only Available Resources: 6 Years Later

Abstract: Rapid response teams have been introduced to intervene in the care of patients whose condition deteriorates unexpectedly by bringing clinical experts quickly to the patient’s bedside. Evidence supporting the need to overcome failure to deliver optimal care in hospitals is robust; whether rapid response teams demonstrate benefit by improving patient safety and reducing the occurrence of adverse events remains controversial. Despite inconsistent evidence regarding the effectiveness of rapid response teams, conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
7

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 45 publications
0
24
0
7
Order By: Relevance
“…65 A 6-year study of an ICU nurse-led RRT reported sustained reductions in cardiopulmonary arrests. 66…”
Section: Rrt Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…65 A 6-year study of an ICU nurse-led RRT reported sustained reductions in cardiopulmonary arrests. 66…”
Section: Rrt Compositionmentioning
confidence: 99%
“…In contrast, a retrospective observational study comparing ICU‐led and resident physician‐led RRT found no difference in cardiac arrests, ICU admissions, or hospital mortality . A 6‐year study of an ICU nurse‐led RRT reported sustained reductions in cardiopulmonary arrests …”
Section: Introductionmentioning
confidence: 95%
“…There is currently little evidence to guide recommendations regarding RT staffing composition, except that responses to deterioration are more likely to be effective when a clinician with critical care skills is leading the RT event (McNeill & Bryden, ). Whether RT should be medical specialist‐led (Al‐Qahtani et al., ), primary care team‐led (Howell et al., ; Moldenhauer, Sabel, Chu, & Mehler, ) or nurse specialist‐led (Mitchell, Schatz, & Francis, ; Pirret, Takerei, & Kazula, ) is unclear. Other variations in RT composition occur between organisations according to “individualised” predetermined clinical parameters and recommended responses (Psirides, Hill, & Hurford, ), which again are adapted locally to align with relevant policies protocols and resources (Australian Commission on Safety and Quality in Healthcare ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a retrospective chart review indicated that before implementation of the RRT, the percentage of cardiopulmonary arrests was 83% or 1.84 per 1000 discharges and mortality was 1.42 per 1000 discharges whereas after RRT implementation, cardiopulmonary arrests decreased to 12.7% or 1.7 per 1000 discharges and hospital mortality decreased to 1.25 per 1000 discharges. 3 Certainly the success of the RRT relies on staff awareness and willingness to activate it. Our initial diffi culties with RRT activation are refl ected in the review of the literature.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…1 Most in-hospital arrest states are caused by respiratory compromise and hypotension. [2][3][4] RRTs were based on the finding that caregivers outside of intensive care units (ICUs) often were unable to recognize these and other early signs and symptoms of patients' deteriorating condition or waited too long to call for assistance to prevent a cardiac arrest, which can occur up to 6 hours before a code blue situation. 1,[4][5][6] At the first sign of deterioration, RRT activation brings critical interventions to the bedside, including a team of multidisciplinary critical care providers and resources 4,7 (Table 1).…”
mentioning
confidence: 99%